Preparation, stability and in vitro evaluation of liposomes containing chloroquine / Stephnie Nieuwoudt - Nieuwoudt, Stephnie (North-West University, 2011)
Malaria is currently a huge treat worldwide, as far as infections are concerned, and is responsible for thousands of deaths per annum. The dilemma associated with the development of anti–malarial drug resistance over the past few decades should be addressed as a matter of urgency. Novel drug delivery systems should be developed in order to employ new and existing anti–malarial drugs in the treatment and management of malaria. The aim of these delivery systems should include an improvement in the efficacy, specificity, acceptability and therapeutic index of anti–malarial drugs. Previous studies have suggested that liposomes have the ability to encapsulate, protect and to promote the sustained release of anti–malarial drugs. Two liposome formulations, namely liposomes and chloroquine entrapped in liposomes, were formulated during this thesis and evaluated by conducting a stability study and an in vitro study with the main focus on cell viability. The stability study consisted of a series of stability tests regarding the stability of nine liposome and nine chloroquine entrapped in liposome formulations over a period of twelve weeks. The in vitro study included three assays such as a reactive oxygen species assay, a lipid peroxidation assay and a hemolysis assay. The aims of these studies included the manufacturing of liposomes, the incorporation of chloroquine into liposomes, the determination of the stability of the formulations as well as the evaluation of the possible in vitro toxicity of liposomes. Results obtained from these studies revealed that liposomes remained more stable over the stability study period in comparison to chloroquine entrapped in liposomes. The entrapment of chloroquine within liposomes was possible, although the initial entrapment efficiency (%) of 14.55 % was much too low. The production of reactive oxygen species occurred to a small extent in the red blood cells and the infected red blood cells. Equal amounts of reactive oxygen species (%) was observed within both the red blood cells and the infected red blood cells with a maximum value of 23.27 % in the presence of the chloroquine entrapped in liposomes at varying concentrations. Red blood cells experienced the highest degree of lipid peroxidation (%) in the presence of chloroquine, at varying concentrations, entrapped in liposomes. The maximum amount of lipid peroxidation (%) was 79.61 %. No significant degree of hemolysis (%) was observed in the red blood cells neither in the presence of the liposomes nor in the presence of the chloroquine entrapped in liposomes at varying concentrations. It can be concluded that liposomes are a more stable formulation and have less toxic effects on red blood cells and infected red blood cells in comparison to the chloroquine entrapped in liposome formulations. Future studies should investigate the possibility of a more stable and less toxic chloroquine entrapped in liposome formulation. === Thesis (M.Sc. (Pharmaceutics))--North-West University, Potchefstroom Campus, 2011.